1979
DOI: 10.7326/0003-4819-90-1-63
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Hyperalimentation: An Alternative to Central Venous Hyperalimentation

Abstract: Severe protein-energy undernutrition is a frequent finding among chronically ill patients. Its causes are anorexia, hypermetabolism, and malabsorption. Adverse consequences include impaired cell-mediated immunity increased susceptibility to infection, poor wound healing, weakness, and death. Spontaneous oral intake is inadequate in patients with this disorder, and therapeutic maintenance or repletion alimentation is needed. Enteral hyperalimentation is the method of choice, if tolerated. A successful treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
1

Year Published

1980
1980
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(52 citation statements)
references
References 23 publications
0
51
0
1
Order By: Relevance
“…In all clinical situations in which it has been studied (5)(6)(7), loss of> 40% ofbaseline BCM is associated with death. This has led us (8) and others ( 1,9) to suggest that loss ofBCM is an important marker ofphysiologic health and a potential nonchronologic marker of aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all clinical situations in which it has been studied (5)(6)(7), loss of> 40% ofbaseline BCM is associated with death. This has led us (8) and others ( 1,9) to suggest that loss ofBCM is an important marker ofphysiologic health and a potential nonchronologic marker of aging.…”
Section: Introductionmentioning
confidence: 99%
“…For example, serum from septic humans can cause catabolism when incubated with muscle from healthy rats (10,11 ). Since septic sera contain TNF-a and IL-I#, it has been suggested that these are the inflammatory mediators that lead to loss of BCM in cancer and infectious diseases such as AIDS( 1, 1 [1][2][3][4][5][6][7][8][9][10][11][12][13]. However, other studies have failed to show a direct catabolic effect of these cytokines in animals, and the existence ofother mediators has been postulated (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…A significant reduction in medical cost can be achieved [5][6][7][8][9]. We report our experience with 61 consecutive patients in whom percutaneous gastrostomies were performed by using two systems designed specifically for enteral feeding distal to the ligament of Treitz.…”
Section: H Carey1mentioning
confidence: 99%
“…Its incidence occurs in up to 30% of patients being fed on general medical and surgical wards (Heymsfield et al 1979;Heibert et al 1981;Cataldi-Betcher et al 1983) and in up to 63% of patients in intensive care units (Kelly et al 1983). In an average 500-bed hospital there will be at least thirty patients receiving nutritional support at any one time, of whom twenty-four will be being enterally fed.…”
mentioning
confidence: 99%